2018
DOI: 10.3892/mmr.2018.9024
|View full text |Cite
|
Sign up to set email alerts
|

Dioscin protects against coronary heart disease by reducing oxidative stress and inflammation via Sirt1/Nrf2 and p38 MAPK pathways

Abstract: Cardiovascular diseases are common diseases in Sweden as in most countries. In 2016, 25,700 persons suffered from coronary heart disease (CHD) and 25% of these died within 28 days. The present study investigated whether dioscin may exert protective effects against CHD‑induced heart apoptosis, oxidative stress and inflammation in a pig model and the potential underlying mechanisms. Adult pigs were used to establish a CHD model group and 80 mg/kg dioscin was administered for 4 weeks. Histological analysis and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 37 publications
2
44
0
Order By: Relevance
“…We conclude from this study that the neuroprotective effects of diosgenin are mainly exerted through a reduction in the oxidative stress response and the enhancement of the oxidative defence system. The results confirmed previous findings regarding the therapeutic effects of diosgenin [39,40]. Histological analysis showed that the biochemical changes in STZ-induced diabetic mice included degeneration of sciatic nerve fibres and endometrial edema.…”
Section: Discussionsupporting
confidence: 90%
“…We conclude from this study that the neuroprotective effects of diosgenin are mainly exerted through a reduction in the oxidative stress response and the enhancement of the oxidative defence system. The results confirmed previous findings regarding the therapeutic effects of diosgenin [39,40]. Histological analysis showed that the biochemical changes in STZ-induced diabetic mice included degeneration of sciatic nerve fibres and endometrial edema.…”
Section: Discussionsupporting
confidence: 90%
“…Tai Chi belongs to a kind of aerobic exercise and should have similar function in regulating fat metabolism. MAPK pathway plays an important role in the pathogenesis of CHD [31] and is regulated by miR-126 [34]. e present findings demonstrated that Tai Chi intervention reduced the relative levels of miR-126 ( Figure 1) and the levels of MAPK signaling (Figures 2 and 3).…”
Section: Discussionsupporting
confidence: 55%
“…However, the related molecular mechanism of Tai Chi exercise remains unclear. Mitogen-activated protein kinase (MAPK) signaling plays a critical role in the pathogenesis of CHD [31,32] and can be activated by miR-126 [33,34]. miR-126 is an independent risk factor of CHD and affects many important gene expression [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, many effects of SIRT1 that are relevant to the suppression or avoidance of inflammation have been also observed upon treatment with melatonin (Figure ). In addition to the inhibition of NF‐κB activation, to Nrf2 upregulation, and to the avoidance of NLRP3 inflammasome activation, several further anti‐inflammatory actions of SIRT1 have become known. This concerns, for example, an inhibition of TLR4, which was demonstrated in renal collecting duct cells by either SIRT1 overexpression or activation by SRT1720, effects that were blocked by Sirt1 siRNA or the sirtuin inhibitors sirtinol and EX527 .…”
Section: Downstream Factors Of Melatonin's Actions With Relevance To mentioning
confidence: 99%